The evolving landscape of high-performance coaching: A synthesis of research on general and context-specific issues - Zhang, J. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The article critically evaluates high-performance coaching, underscoring its capacity to cultivate accountability and self-awareness for peak individual performance. It discusses obstacles including identity shifts, and work-life equilibrium, which disproportionately impact marginalized sectors, championing the need for additional scholarly investigation in this field.